Associations Between Unmet Social Needs and Overactive Bladder. Issue 5 (15th November 2022) - Sebesta, Elisabeth M.; Gleicher, Stephanie; Kaufman, Melissa R.; Dmochowski, Roger R.; Reynolds, W. Stuart
Abstract : Abstract : Purpose: There is growing interest in how social determinants of health may explain relationships between social conditions and health. Overactive bladder is common in the United States, posing a significant public health burden. It was the goal of the present study to assess whether overactive bladder was associated with unmet social needs in a large, cross-sectional sample of patients. Materials and Methods: A community-based sample of adults was recruited electronically to complete questionnaires on clinical and demographic information, urinary symptoms and unmet social needs. Multivariable logistic regression was used to assess for association between overactive bladder and multiple unmet social needs. Results: The sample of 3, 617 participants had a mean±SD age of 47.9±17.3 years. The majority of participants identified as White, non-Hispanic (83.5%), and female (77.6%). A total of 1, 391 patients (38.5%) were found to have overactive bladder. The presence of overactive bladder was associated with numerous unmet social needs, including housing instability, food insecurity, worry about utilities, lack of transportation, skipping medical appointments, needing legal help, stress in personal relationships, worry about toilet access and plumbing at home, and lack of social supports. On multivariable analysis adjusting for multiple covariates, all associations between overactive bladder and social needs remained significant. Conclusions: Multiple unmet social needs were associated with overactive bladder, which may have implications for the overall management of overactive bladder patients. It is important for providers to consider these unmet social needs of patients, as highlighting and addressing these factors hopefully can help improve care of individuals with overactive bladder.